Large-area commercial-grating-quality subwavelength periodic ripples on silicon efficiently fabricated by gentle ablation with femtosecond laser interference via two cylindrical lenses. (November 2020) - Cao, Kaiqiang; Chen, Long; Wu, Haochen; Liu, Jukun; Cheng, Ke; Li, Yanli; Xia, Yingjie; Feng, Chaopeng; Zhang, Shian; Feng, Donghai; Sun, Zhenrong; Jia, Tianqing
Highlights: This study presents a new strategy for efficiently fabricating unlimited large-area nanogratings composed of subwavelength periodic ripples on a silicon wafer with high quality similar to commercial gratings. The fabrication efficiency was enhanced by 2–3 orders by the coherent resonance-enhanced surface plasmon polariton via gentle ablation irradiated by femtosecond laser. High-quality nanogratings were fabricated by two-beam interference via cylindrical lenses with a small cross angle, which could be an inexpensive potential application in the industry. Abstract: This paper presents a new strategy for efficiently fabricating large-area subwavelength periodic ripples with commercial grating quality on a silicon surface. Two laser beams of 800 nm, 50 fs at a repeat frequency of 1 kHz were focused on a silicon wafer via two cylindrical lenses. The spacing of the interference fringes was adjusted to excite a coherent resonance-enhanced (CRE) surface plasmon polariton (SPP). The CRE SPP efficiently induced homogeneous and extremely straight periodic ripples through gentle ablation, which avoids substantial debris and reduces the roughness of the periodic ripples. At the two edges of the ablation band after single scanning, the ripples were shallow, spaced, and exceptionally straight, which is greatly advantageous in the preparation of large-area gratings line by line. The subwavelength periodic ripples were fabricated on a silicon wafer with a diameter of 100 mm by scanning at a speed of 2 mm/s and a spacing of 1.55 mm. Compared with the alternating amorphous-crystalline ripples induced by a single laser beam, the fabrication efficiency was enhanced by 2–3 orders. Measurements with a confocal optical microscope and white light diffraction demonstrate that the periodic ripples were extremely straight, smooth, and homogeneous, similar to the gold gratings. The diffraction resolution of the nanogratings of subwavelength periodic ripples was nearly as narrow as that of commercial gratings.